Halal cosmetic critical ingredients: an overview of animal based ingredients / ‘Aina Fariha Mohamad Hussaini, Nurfarhani Zarmani and Nor Amin Mohd Noor - Mohamad Hussaini, ‘Aina Fariha; Zarmani, Nurfarhani; Mohd Noor, Nor Amin (UiTM Cawangan Johor, 2024)
The halal cosmetics market is rapidly expanding and offers a unique perspective on the beauty and personal care industries. With an emphasis on goods that comply to Islamic principles and values, the market is growing as customers seek halal-certified cosmetics that correspond with their religious and ethical views. Since the production and manufacturing of cosmetics is dominated by non-halal cosmetic manufacturers, there is no guarantee that they use all halal ingredients in the making of cosmetic products. Not all manufacturers will disclose the source of the animal-based ingredients of their cosmetic products. There is a high possibility that the animal-based ingredients in the cosmetic products made of non-halal animal such as pig or its derivatives or from halal animal that is not slaughtered according to Islam. Therefore, this paper summarizes existing literature on critical ingredients used in the manufacturing of halal cosmetics. The identification of the status of critical cosmetic ingredients may provide a technical guideline among manufacturing in complying the raw material control requirements ofthe Malaysia Halal Management System (NfHMS). Keywords: Animal, Halal Cosmetic, Ingredients, Zooceuticals